PUBLIC PERCEPTIONS ON THE CONSERVATION OF NATURAL RESOURCES AND ECOSYSTEMS (Case Study In Central Park District Of South Siberut Mentawai Islands) - Sakeletuk, Julius Ngaire; Erita, Yeni; Juita, Erna (Pendidikan Geografi, 2013)
The research was motivated by the illegal loggers, rampant poaching primates endemic National Park of Siberut in Siberut Selatan District, and wildlife trade is done by people who were around the National Park of Siberut in Siberut Selatan District. This study aims to obtain data, information and an overview of public perception on the Conservation of Natural Resources and Ecosystems in Central Park District of South Siberut Siberut Mentawai Islands regency views of: 1) the implementation of the conservation of natural resources and ecosystems, 2) efforts to preserve heritage conservation of natural resources and ecosystems for future generations, and 3) barriers that prevent the implementation of the conservation of natural resources and ecosystems in National Park of Siberut in Siberut Selatan District.This research is a descriptive study. The population in this study were all heads of families residing in the District of South Siberut Mentawai Islands regency. Based on recent data the population of 1500 inhabitants with 800 families (KK). The research sample was taken with a proportional random sampling method with the proportion of 10% that the sample in this study amounted to 80 families.The research found that: 1) the public perception on the Conservation of Natural Resources and Ecosystems in Siberut National Park includes the Mentawai Islands with a good percentage of 79.6%, 2) Public perception of the effort to preserve the heritage of Conservation of Natural Resources and Ecosystems in the Garden Siberut National Metntawai Islands District including well with the percentage of 78.67%, and 3) the public perception of the barriers experienced in the implementation of the Natural Resources Conservation and Ecosystem National Park Siberut Mentawai Islands including well with the percentage of 77.27%Â